Follow Up Report of Examination Result Of Supreme Audit Agency For State Financial Management: Tindak Lanjut Laporan Hasil Pemeriksaan Badan Pemeriksa Keuangan - Citra Nasir (Al-Mahkamah: Jurnal Hukum, Politik dan Pemerintahan, 2024)
The purpose of this research is to determine the implementation of follow-up reports on the results of the Supreme Audit Agency's audit of state financial management. It is hoped that the follow-up to the Audit Result Report from the Supreme Audit Agency will be a way to find out and overcome the occurrence of state losses committed by state financial managers. Even though state finances are not saved from "losses", it is beneficial to have no accountability after state finances experience "losses". The research method uses normative legal research using a statutory and regulatory approach and a conceptual approach. The results of the research obtained conclusions about the follow-up to the financial audit agency's audit report, namely: a) Political action, contained in the follow-up to recommendations aimed at improving the management system and accountability of state finances, as well as resolving compensation through treasury demands; and b) Juridical follow-up, contained in the follow-up carried out by law enforcement officials in the Audit Results Report of the Supreme Audit Agency which contained state losses. To find out the extent of recommendations, settlement of compensation for state/regional losses, handling of BPK audit findings submitted to the authorized agencies which are followed up by Representative Institutions and Government Agencies regarding the findings and in the Financial Audit Results Report, you can see the Summary of Semester Audit Results.